2019
DOI: 10.1186/s12885-019-5319-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of adipose tissue and muscle mass in advanced colorectal cancer: a post hoc analysis of two non-randomized phase II trials

Abstract: BackgroundThe prognostic value of body composition in cancer patients has been widely studied during the last decade. The main finding of these studies is that sarcopenia, or skeletal muscle depletion, assessed by CT imaging correlates with a reduced overall survival (OS). By contrast, the prognostic value of fat mass remains ill-defined. This study aims to analyze the influence of body composition including both muscle mass and adipose tissue on OS in a homogeneous population of advanced colorectal cancer (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 34 publications
1
101
0
1
Order By: Relevance
“…However, although several studies have revealed an association between SM and severe or infectious postoperative complications , a lack of association with severe postoperative complications was found in other studies . Muscle density was found to be associated with long‐term overall survival , in contrast to other studies . For VAT, the association with prolonged LOS showed both positive and negative results .…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, although several studies have revealed an association between SM and severe or infectious postoperative complications , a lack of association with severe postoperative complications was found in other studies . Muscle density was found to be associated with long‐term overall survival , in contrast to other studies . For VAT, the association with prolonged LOS showed both positive and negative results .…”
Section: Introductionmentioning
confidence: 67%
“…This inconsistency is in line with available literature. Low muscle density has been associated with postoperative complications and long‐term survival , although other studies have found no associations with overall or severe postoperative complications and long‐term survival . The same counts for VAT or visceral obesity, which was found to be associated with postoperative complications , LOS , readmission , and 2‐year survival in some studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, depending on the moment the patient is evaluated, PG-SGA will not be effective to correlate with survival (17,35) . It is observed that changes in body composition (36) , such as body fat in FIGURE 1B, can be related to the survival of the patient with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Přítomnost sarkopenie ještě před dia gnózou CRC (tedy v době screeningové kolonoskopie) pozitivně koreluje s přítomností pokročilého onemocnění, které se najde dalším vyšetřováním [20][21][22]. Podle výsledků četných studií koreluje přítomnost sarkopenie u nemetastatického CRC v předoperačním období s výskytem operačních komplikací a horší prognózou [23][24][25][26]. Sarkopenie je také spojena s horší prognózou u starších pacientů léčených neoadjuvantní nebo adjuvantní chemoradioterapií pro karcinom rekta [27,28].…”
Section: Sarkopenie a Systémová Léčba Mcrcunclassified